Synthesis, characterization and thermal behaviour of solid-state compounds of 2-methoxybenzoate with some bivalent transition metal ions - de Carvalho, Cláudio Teodoro; de Siqueira, Adriano Buzutti; Rodrigues, Emanuel Carlos; Ionashiro, Massao (Eclética Química, 2005)
Solid-state M-2-MeO-Bz compounds, where M stands for bivalent Mn, Co, Ni, Cu and Zn and 2-MeO-Bz is 2-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry-differential thermal analysis (TG-DTA), thermogravimetry, derivative thermogravimetry (TG/DTG), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to have information about the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds.